Metabarcoding reveals the differential sensitivity of planktonic microbiome to environmental filtering and biointeraction in Sansha Yongle blue hole - Chen, Tianying; Zhuang, Yunyun; Chen, Chang; Mao, Xuewei; Ge, Ruping; Chen, Hongju; Chen, Jianwei; Fu, Liang; Yang, Zuosheng; Liu, Guangxing (Frontiers in Marine Science, 2022)
The Sansha Yongle blue hole (SYBH) is the world’s deepest blue hole known so far and its unique hydrochemical characteristics make it a valuable site for studying biodiversity and ecological processes. Here, we used metabarcoding approach to investigate the diversity, assembly mechanism and co-occurrence pattern of planktonic microbiome in SYBH. Our results revealed the distinct separation of communities from upper oxic, middle oxic and suboxic-anoxic layer and significant day-night difference was detected in the upper-layer community of microeukaryotes, indicating potential diel migration. Stochastic processes played a significant role in the community assembly of microeukaryotes, while deterministic processes dominated in prokaryotes, confirming the stronger environmental filtering on prokaryotes as also suggested by the correlation with environmental variables. Microeukaryotes were less sensitive to environments but significantly affected by cross-domain biointeraction. When comparing the subcommunities of different abundance, we found that abundant taxa were widespread while rare taxa were habitat-specific. In co-occurrence network, over 87% of the interactions and 19 out of 20 keystone OTUs (Operational Taxonomic Units) were affiliated to moderate or rare taxa, suggesting the importance of non-abundant taxa in maintaining community stability. The predominant positive edges in the network pointed to that interspecies cooperation may be one of the ecological strategies in SYBH. Overall, we highlight the divergent assembly pattern and different driving forces in shaping plankton microbiome in SYBH, which may advance current understanding on diversity and dynamics of marine life in blue hole ecosystems.